2019
DOI: 10.1101/726026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Axon-like protrusions promote small cell lung cancer migration and metastasis

Abstract: 14Metastasis is the main cause of death in cancer patients but remains a poorly understood 15 process. Small cell lung cancer (SCLC) is one of the most lethal and most metastatic types of 16 human cancer. SCLC cells normally express neuroendocrine and neuronal gene programs but 17 accumulating evidence indicates that these cancer cells become relatively more neuronal and less 18 neuroendocrine as they gain the ability to metastasize. Here we show that mouse and human 19 SCLC cells in culture and in vivo can… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…In particular, we found that variant (non-SCLC-A) SCLC subtypes are enriched in local/distant SCLC metastases in humans, with SCLC-N upregulating pathways in EMT, axonogenesis, and metastasis 20 . These findings are consistent with 1) a previously reported mouse model with invasive and metastatic SCLC tumors overexpressing NEUROD1 17 and 2) cell lines with an axonogenic phenotype that correlates with NEUROD1 expression and promotes metastasis 33 . In contrast to SCLC-A, we found an enrichment of ligand-receptor interactions in SCLC-N. One biphenotypic tumor identified ligands secreted from the SCLC-A compartment that activate Notch, Wnt, TGFβ/Activin and pro-axonogenic signaling in SCLC-N.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, we found that variant (non-SCLC-A) SCLC subtypes are enriched in local/distant SCLC metastases in humans, with SCLC-N upregulating pathways in EMT, axonogenesis, and metastasis 20 . These findings are consistent with 1) a previously reported mouse model with invasive and metastatic SCLC tumors overexpressing NEUROD1 17 and 2) cell lines with an axonogenic phenotype that correlates with NEUROD1 expression and promotes metastasis 33 . In contrast to SCLC-A, we found an enrichment of ligand-receptor interactions in SCLC-N. One biphenotypic tumor identified ligands secreted from the SCLC-A compartment that activate Notch, Wnt, TGFβ/Activin and pro-axonogenic signaling in SCLC-N.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we found that SCLC-N was enriched in two main axonogenic signaling pathways: ephrin (EFNB1 and EPHB2, among others) 30 and semaphorin (SEMA6A and NRP2, among others) 31 . Prior studies have shown that the axonogenesis program coordinates cell polarity with neuronal migration 32 ; it has been implicated in SCLC metastasis 33 , but never before in SCLC-N specifically. We have shown that LUAD hijacks endodermal developmental preprint (which was not certified by peer review) is the author/funder.…”
Section: Sclc-n Exhibits a Pro-metastatic Neuronal And Emt Phenotypementioning
confidence: 99%
“…Several novel therapeutic paradigms arise that exploit the neuronal microenvironment and neurodevelopmental characteristics: (a) Prevention of the outgrowth of neurite‐like protrusions to inhibit invasion and interconnection; (b) Inhibition of tumor‐tumor cell communication; (c) Inhibition of neuronal input and neurotransmitter signaling; (d) Depletion of neuronal intratumoral subpopulations and tumor‐subtype specific treatments. Pharmacological or genetic (eg, by antisense oligonucleotides) targeting of neurodevelopmental pathways and molecules, such as Gap43, Fez1 or Ttyh1, could inhibit the outgrowth of neurite like‐protrusions. It remains to be elucidated if these protrusions also play a role for therapy resistance outside the brain, but first evidence exists that demonstrates that the inhibition of neurite‐like protrusions can be used to reduce the metastatic potential 30,33 . Many molecules involved during neurodevelopment seem to be of limited importance in the mature brain and might hence be suitable targets for novel tumor‐specific therapies 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurite‐ and TM‐like protrusions, which are also driven by neurodevelopmental pathways including Gap43, have recently been found in small cell lung cancer (SCLC), 30 where they promoted invasion and metastasis. It needs to be seen whether those protrusions are also used for the formation of multicellular networks and for interconnection with host cells, for example, those of the brain, an organ where these tumors frequently metastasize to.…”
Section: Neurodevelopmental Features Of Extracranial Malignancies Andmentioning
confidence: 99%
“…Several studies had reported similar findings in various cancer types. [53][54][55][56] Finally, according to the detected genetic or epigenetic alterations, a prognosis model was constructed and was found to have a superior performance with a higher C-index or AUC value compared to the previous models. [14][15][16] To our surprise, the trained models showed higher accuracy of 5-year survival prediction on the training sets compared with the result from the 1-year survival prediction, whereas the superiority was lost when the prediction was done using the test set.…”
Section: Discussionmentioning
confidence: 99%